On the functional independence of numerical acuity and visual working memory - Dell’Acqua, Roberto; Sessa, Paola; Brigadoi, Sabrina; Gervain, Judit; Luria, Roy; Doro, Mattia (Frontiers in Psychology, 2024)
Deciding where to direct our vehicle in a crowded parking area or where to line up at an airport gateway relies on our ability to appraise the numerosity of multitudes at a glimpse and react accordingly. Approximating numerosities without actually counting is an ontogenetically and phylogenetically primordial ability, given its presence in human infants shortly after birth, and in primate and non-primate animal species. Prior research in the field suggested that numerosity approximation is a ballistic automatism that has little to do with human cognition as commonly intended. Here, we measured visual working memory capacity using a state-of-the-art change detection task and numerosity approximation using a dot-comparison task, and found a null correlation between these two parametrical domains. By checking the evidential strength of the tested correlation using both classic and Bayesian analytical approaches, as well as the construct validity for working memory capacity and numerosity approximation estimates, we concluded that the present psychophysical evidence was sufficiently strong to support the view that visual working memory and numerosity approximation are likely to rely on functionally independent stages of processing of the human cognitive architecture.